2002
DOI: 10.1046/j.1365-2982.2002.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bowel cleansing on colonic transit in constipation due to slow transit or evacuation disorder

Abstract: Colon transit time measurement with radio-opaque markers is a method of studying the passage of luminal contents throughout the colon. Overall colonic transit time (CTT), as well as segmental transit times [right (RTT), left (LTT) and rectosigmoid (RSTT)], can be calculated. We hypothesize that CTT is influenced by faecal impaction when the rectum is emptied infrequently. The aim of this study is to investigate the effect of bowel cleansing on colonic transit time in patients with chronic constipation. In 25 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Rectal faecal disimpaction was, however, not performed prior to CTT evaluation in our patients. The presence of rectal faecal impaction in our patients possibly affected colonic motor activity in the more proximal colon,26 27 leading to misinterpretation of CTT. We were therefore unable to distil from the transit studies whether delayed transit was caused by true rectal or colonic dysmotility.…”
Section: Discussionmentioning
confidence: 85%
“…Rectal faecal disimpaction was, however, not performed prior to CTT evaluation in our patients. The presence of rectal faecal impaction in our patients possibly affected colonic motor activity in the more proximal colon,26 27 leading to misinterpretation of CTT. We were therefore unable to distil from the transit studies whether delayed transit was caused by true rectal or colonic dysmotility.…”
Section: Discussionmentioning
confidence: 85%
“…Second, most manometry studies are performed after cleansing the colon with a lavage solution before catheter placement, raising concern that observed motor patterns may not reflect those under physiological conditions of fecal retention. In studies in constipation, colon transit times were reduced by a mean of 22 h by an oral lavage solution (30).…”
Section: Discussionmentioning
confidence: 99%
“…Colonic motor patterns in patients with lesser degrees of slow transit are less well characterized. Additionally, most studies have been performed after consumption of lavage solutions to cleanse the colon, which can modify colonic motor patterns (30). IBS patients show inconsistent changes in colonic motor activity both under basal conditions and after stimulation such as with meal ingestion (4,10).…”
mentioning
confidence: 99%
“…Sloots et al (5) reported that bowel cleansing shortened colonic transit time, especially in patients with constipation. Bowel cleansing was performed with Klean-Prep® in both patients and volunteers in their study.…”
Section: Introductionmentioning
confidence: 99%